Health : an ecosystem approach - Lebel, Jean, 1963- (In focus (International Development Research Centre (Canada)), 2003)
Can people remain healthy in a world that is sick? Many ecological disasters can be directly traced to careless exploitation of the environment, with human beings as first perpetrator and then victim. Our health closely mirrors the health of our surroundings: this is the basis of the Ecohealth approach. It recognizes the inextricable links between humans and their biophysical, social, and economic environments, and that these links are reflected in the populations state of health. Reconciling an ecosystems health with the health of its human inhabitants is a new area of research, requiring i.